Institutional Dual-Holders and Managers' Earnings Disclosure - Peyravan, Leila; Wittenberg-Moerman, Regina (The Accounting Review, 2022)
ABSTRACT We investigate how institutional (non-commercial bank) investors that simultaneously invest in a firm's debt and equity (dual-holders) influence the firm's voluntary disclosure. Because institutional dual-holders trade on private information gleaned through lending relationships, we predict and find that borrowers increase earnings forecast disclosure to reduce these investors' information advantage following the origination of loans with their participation. We also show that the increase in disclosure is stronger when the access to a borrower's private information endows dual-holders with a greater information advantage and when the consequences of this access are likely to be more pronounced. We further find that institutional dual-holders earn excess returns when trading equity of non-guider firms following loan origination, but not when firms issue guidance, confirming that earnings disclosure helps level the playing field among investors. Our findings highlight that firms actively use disclosure to mitigate the adverse effect of dual-holders on their information environment.